Impact of Mobile Marketing on Brand Loyalty Towards Gen Z in Bangladesh: Evidence from BKash - Md. Abdullah Al Jamil; Sk Shakil Ahmed Sk Shakil Ahmed; Md. Azmir Hossain (Annals of Management and Organization Research, 2026)
Abstract Purpose: The aim of the study is to investigate the impacts of mobile marketing on the brand loyalty among Generation Z consumers in Bangladesh, by examining four mobile marketing components: mobile phone contact, text message marketing, permission-based SMS marketing, and mobile website content. Research Methodology: This study adopts an explanatory research design within a quantitative, cross-sectional framework. Primary data were collected in Bangladesh through a structured questionnaire administered online and offline to Gen Z bKash users across 36 districts (n = 322; data collection: 1–20 December 2025). Data were analyzed using IBM SPSS and SmartPLS. Results: Mobile marketing in general has a significant impact on brand loyalty. Text message marketing, permission-based SMS marketing, and mobile website content show significant positive effects on brand loyalty, whereas mobile phone contact is not significant. The strongest predictor is permission-based SMS marketing, which points out the importance of consent and trust. Conclusions: Mobile marketing can strengthen Gen Z’s brand loyalty in Bangladesh when it prioritizes permission-based SMS marketing, relevant SMS content, and a user-friendly mobile web experience; intrusive direct phone contact appears less effective. Limitations: Convenience sampling, a single-brand (bKash) focus, and a cross-sectional design may limit generalizability and causal inference. Contributions: This study extends mobile marketing and brand loyalty evidence to an under-researched emerging market and provides guidance for fintech/service marketers on designing consent-based messaging and mobile website experience improvements to build long-term loyalty among Gen Z.